The Use of Learner Autonomy in English as a Foreign Language Context among Saudi Undergraduates Enrolled in Preparatory Year Deanship at Najran University - Falah Alzubi, Ali Abbas; Mehar Singh, Manjet Kaur; Pandian, Ambigapathy (Australian International Academic Centre (AIAC), 2017)
This paper explores the current practices of learner autonomy among Saudi undergraduates at Preparatory Year, Najran University. The Short List questionnaire developed by Dixon (2011) was administered to measure the use of autonomous learning in English as a foreign language (EFL) context. Quantitative data were gathered from 208 male students in level one. The results of the data analysis showed that the participants experience a low level of learner autonomy (LA) in English language. While the LA dimensions of linguistic confidence, social comparison, and locus of control are considered a weakness for the participants, they had medium averages in information literacy, metacognition, and self-reliance dimensions. Therefore, the study suggests the need for pedagogical treatments like the strategy use instruction to develop LA in the Saudi EFL context.